FAKTOR PENYEBAB KECELAKAAN LALU LINTAS PADA SISWA SEKOLAH MENENGAH ATAS DI KOTA SAMARINDA - Dina Lusiana Setyowati; Ade Rahmat Firdaus; Nur Rohmah Rohmah (Universitas Airlangga, 2018)
Road accidents were the main causes of mortality at young ages, especially for gentlemen, it can also caused physical disabilities. Mortality rates which happened at young ages were caused by the low rates of their awareness perception due to the harm on traffic. This research was conducted to depict the causes of road accidents and safety riding while using vehicles of senior high school students in Samarinda. This research was conducted in nine senior high school which were chosen to represent each district. The total respondents were 315, which were taken using proportional random sampling, each district were represented by one school. The characteristic of respondents in this research was the students in 10th grade, who ride motorcycles to school. The data were collected using questionnaire, to avoid any bias, it was helped by enumerators. Each enumerator monitored 10 respondents. The data were analyzed using chi square with α 0.05%. The results showed that the accidents rate was 30.8%, the rates of using motorcycle due to has none to accompany were 39,4%, due to the long distance were 11.7%. There was relationship between accident rates and safety riding. The relationship between accident and rebelling yellow lamp was p = 0.015, calling p = 0.041, sending SMS p = 0.000, smoking p = 0.01 and riding with more than two p = 0.043. Meanwhile riding with more than 60 km/h speed, listening to the music, out of the street line, disobey the traffic signs have no relationship with road accidents. Factors that cause accidents are driving behavior called warning lights, using the phone, smoking and more than two people while driving.Keywords: accident, high school, riding